Study on the effect of aqueous leaf extract of Anacardium occidentale on seed germination and seedling growth of Vigna unguiculata - Parayil, Sheeja P; Honey, A; Abhilash, ES (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
Allelochemicals play a significant role in the germination and seedling growth of crop plants. Various allelochemicals are present in Anacardium. These chemicals enter into the crops environment and adversely affect the growth of crop and reduce their yield. It is seen that with increase in the concentration of leaf extract there is a decrease in germination value, germination percentage, cumulative germination percentage, shoot length , root length, leaf area, fresh weight, dry weight and stomatal index. For the successful cultivation of cowpea, the seeds should be grown away from this plant. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9504 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 10-14